Penerapan Metode Economic Order Quantity (EOQ) Dan Reorder Point (ROP) Pada Pengendalian Persediaan Bahan Baku Di UMKM Dapur Bunga Berbintang - Juwita Juwita; Fitri Rahmiyatun (Politeknik Negeri Ambon, 2023)
UMKM Dapur Bunga Berbintang, a business engaged in the culinary sector, serves various types of products such as boxed rice and snack boxes wet cakes which require a more effective and efficient raw material inventory control strategy. The raw materials analyzed are Thai Cassava raw materials, consisting of cassava, cornstarch, coconut milk, and pandan leaves. The problem faced by UMKM Dapur Bunga Berbintang is the inappropriate control of raw material requirements. The purpose of this study is to understand the stages of controlling Thai Cassava raw materials according to UMKM policies and the EOQ model. The method applied in this research is descriptive qualitative. The data needed in this study are the total use of raw materials, ordering costs, storage costs, order frequency, and the time to obtain raw materials. The results of the study state that the EOQ calculation purchases 39.6 kg of cassava raw materials, 403.07 grams of cornstarch, 27.731 pcs of coconut milk, and 23.77 pieces of pandan leaves. The total cost of raw material inventory applying EOQ can save IDR 448,227. The ordering frequency obtained from EOQ is 5 times a year. Safety inventory of 5 kg of cassava raw materials, 54 grams of cornstarch, 4 pcs of coconut milk, and 3 sheets of pandan leaves. And the reorder time is 30 kg of cassava, 300 grams of cornstarch, 21 pcs of coconut milk, and 21 sheets of pandan leaves.